How Word Meaning Influences Word Reading. (August 2015) - Taylor, J. S. H.; Duff, Fiona J.; Woollams, Anna M.; Monaghan, Padraic; Ricketts, Jessie
Understanding how we read is a fundamental question for psychology, with critical implications for education. Studies of word reading tend to focus on the mappings between the written and spoken forms of words. In this article, we review evidence from developmental, neuroimaging, neuropsychological, and computational studies that show that knowledge of word meanings is inextricably involved in word reading. Consequently, models of reading must better specify the role of meaning in skilled reading and its acquisition. Further, our review paves the way for educationally realistic research to confirm whether explicit teaching of oral vocabulary improves word reading.